SOCIAL DESIGN IN THE PROCESS OF MANAGING A PRESCHOOL EDUCATIONAL ORGANIZATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The modern system of preschool education requires the introduction of innovative forms of management that will ensure not only the fulfillment of educational standards, but also the full development of the child's personality. Social design is becoming an effective tool in the management of an educational organization, since it is aimed at creating conditions for cooperation between all participants in the educational process, developing the personal potential of preschoolers, and implementing socially significant initiatives. The article examines the theoretical aspects of social design, reveals its functions, goals and objectives, and describes practical approaches to its implementation in the management structure of a preschool institution.